2015
DOI: 10.1111/dme.12976
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of pharmacist‐managed services in people with diabetes mellitus: a systematic review

Abstract: Pharmacist-managed services had a positive return in terms of economic viability. With the expanding role of pharmacists in the healthcare sector, alongside increasing health expenditure, future economic studies of high quality are needed to investigate the cost-effectiveness of these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
2
57
1
1
Order By: Relevance
“…Diabetes, a metabolic disorder with rapid emerging epidemic, accounts for a total of 387 million global population living with diabetes till 2014 (1). It is associated with substantial indisposition toward other illnesses and a major risk factor for cardiovascular disease, stroke, and renal complications (1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes, a metabolic disorder with rapid emerging epidemic, accounts for a total of 387 million global population living with diabetes till 2014 (1). It is associated with substantial indisposition toward other illnesses and a major risk factor for cardiovascular disease, stroke, and renal complications (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with substantial indisposition toward other illnesses and a major risk factor for cardiovascular disease, stroke, and renal complications (1). According to the National Health and Morbidity Survey (NHMS) 2011, “the prevalence of diabetes in Malaysia had amplified relatively from 15.2% (2011) to current 17.5%, compared to the relative increase of 31.0% between 2006 (prevalence: 11.6%) and 2011” (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists are capable of providing a wide range of services that can reduce health care costs, such as proper drug counseling, selfmanagement support, drug-related problem identification, effective patient education, and training on blood glucose and blood pressure monitoring. [19][20][21][22][23][24] The role of pharmacists in patient care was extensively investigated by Rotta et al 25 A systematic review of 269 randomized controlled trials on pharmacist-delivered patient care clearly demonstrated that clinical services offered by pharmacists positively impact health-related outcomes. In addition, the role of the pharmacists' clinical services in chronic disease management was clearly demonstrated in 1996 in the Asheville project.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated that when pharmacists are added to the health care team in providing diabetes management, an improvement in glycosylated hemoglobin (A1C) is seen. 16,17 An important component of patient-centered care is shared decision-making characterized by effective patient-provider communication, where patients weigh treatment choices in light of the potential benefit and harm and arrive at informed preferences. 4,[9][10][11][12][13][14][15] Incorporating clinical pharmacists into the care team has demonstrated cost savings and improved quality-adjusted life years.…”
Section: Introductionmentioning
confidence: 99%